2023
DOI: 10.21203/rs.3.rs-2429460/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), and monocyte-to-lymphocyte ratio (MLR), and eosinophil-to-lymphocyte ratio (ELR) as biomarkers in patients with acute exacerbation chronic obstructive pulmonary disease

Abstract: The study comprehensively evaluated the prognostic roles of the platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio. (MLR), basophil-to-lymphocyte ratio (BLR) and eosinophil-to-lymphocyte ratio (ELR) in patients with acute exacerbation chronic obstructive pulmonary disease (AECOPD). 619 patients with AECOPD and 300 healthy volunteers were retrospectively included into the study. The clinical characteristics containing laboratory findings of the AECOPD patients… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Unlike PLR, NLR, and MLR, ELR was identi ed to be a favourable prognostic factor in AECOPD. Namely, elevated ELR was associated with better clinical outcomes, such as reduced hospital LOS as well as inhospital mortality, and alleviated air ow limitation [3]. In this study, increased ELR was associated with improved OS and reduced ICU admission rates, and ELR was positively correlated with hospital LOS as well as ICU LOS.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Unlike PLR, NLR, and MLR, ELR was identi ed to be a favourable prognostic factor in AECOPD. Namely, elevated ELR was associated with better clinical outcomes, such as reduced hospital LOS as well as inhospital mortality, and alleviated air ow limitation [3]. In this study, increased ELR was associated with improved OS and reduced ICU admission rates, and ELR was positively correlated with hospital LOS as well as ICU LOS.…”
Section: Discussionsupporting
confidence: 52%
“…To our best knowledge, this was the rst study to evaluate the prognostic value of the systemic in ammatory factors (PLR, NLR, MLR, BLR, and ELR) in patients with SCAP. BLR is a rarely studied disease biomarker, a recent study on the association of systemic in ammatory factors (PLR, NLR, MLR, BLR, and ELR) with clinical outcomes in patients with AECOPD revealed that only BLR had no association with the clinical outcomes involving hospital LOS, air ow limitation, and in-hospital mortality [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, elevated ELR was associated with better clinical outcomes, such as reduced hospital LOS as well as inhospital mortality, and alleviated air ow limitation. 3 In this study, increased ELR was associated with improved OS and reduced ICU admission rates, and ELR was positively correlated with hospital LOS as well as ICU LOS. Moreover, ELR were lowered in patients with SCAP compared to healthy volunteers, and improved when the patients were in recovery after treatment.…”
Section: Discussionmentioning
confidence: 51%
“…BLR is a rarely studied disease biomarker, a recent study on the association of systemic in ammatory factors (PLR, NLR, MLR, BLR, and ELR) with clinical outcomes in patients with AECOPD revealed that only BLR had no association with the clinical outcomes involving hospital LOS, air ow limitation, and in-hospital mortality. 3 Nevertheless, this study found that BLR was served as an important biomarker in SCAP. In patients with SCAP, elevated BLR was associated with increased in-hospital mortality, ICU admission rates, and ICU mortality.…”
Section: Discussionmentioning
confidence: 71%